Divergent Effects of Systemic and Intracollicular CB Receptor Activation Against Forebrain and Hindbrain-Evoked Seizures in Rats - Santos, Victor R.; Hammack, Robert; Wicker, Evan; N’Gouemo, Prosper; Forcelli, Patrick A. (Frontiers in Behavioral Neuroscience, 2020)
Cannabinoid (CB) receptor agonists are of growing interest as targets for anti-seizure therapies. Here we examined the effect of systemic administration of the CB receptor agonist WIN 55,212-2 (WIN) against audiogenic seizures (AGSs) in the Genetically Epilepsy Prone Rat (GEPR)-3 strain, and against seizures evoked focally from the Area Tempestas (AT). We compared these results to the effect of focal administration of the CB1/2 receptor agonist CP 55940 into the deep layers of the superior colliculus (DLSC), a brain site expressing CB1 receptors. While systemic administration of WIN dose-dependently decreased AGS in GEPR-3s, it was without effect in the AT model. By contrast, intra-DLSC infusion of CP 55940 decreased seizures in both models. To determine if the effects of systemic WIN were dependent upon activation of CB1 receptors in the DSLC, we next microinjected the CB1 receptor antagonist SR141716, before WIN systemic treatment, and tested animals for AGS susceptibility. The pretreatment of the DLSC with SR141716 was without effect on its own and did not alter the anti-convulsant action of WIN systemic administration. Thus, while CB receptors in the DLSC are a potential site of anticonvulsant action, they are not necessary for the effects of systemically administered CB agonists.